O papel do professor de educação especial na proposta do coensino - Zerbato, Ana Paula (Universidade Federal de São Carlos, 2014)
The collaborative teaching or co-teaching is a specific service delivery option in which a general educator and a specialized one share the responsibility for planning, instruction and evaluation of teaching for a heterogeneous group of students. This support service arose as an alternative to the Multifunctional Resources Room (SRM), special classes or special schools work, has been adopted in many countries and has been pointed out as one of the most promising support services to facilitate the education of students with disabilities in regular classrooms of General Education settings. In Brazil, this type of service is still little known, mainly because it has not been recommended by the Special Education Policy, which has prioritized the support of a regular extra-class specialized teacher, through what has been called specialized educational (AEE) services, offered in resources room. This study, conducted in a town upstate São Paulo which has implemented a support service based on the co-teaching model since 2011, aimed at defining the role of Special Educators within coteaching approach according to the perspective of multiple agents heard in the process of school inclusion, namely: General Educators, Special Educators, coordinators, principals, vice-principals, parents and students. For this descriptive study, were interviewed 21 people (six General Education teachers, four Special Education teachers, six parents of students with disabilities, three principals, one vice-principal and one educational coordinator) from five schools adopting this service model. The presented results describe, among other things, the challenges of teaching Special Education students in general classrooms, the perceptions of the school agents about co-teaching, the ways co-teaching is developed considering their reality and how these agents define the role of Special Educators and General Educators based on the co-teaching approach. Overall data corroborate the literature on co-teaching since participants evaluated positively this service provision model. It is expected that this research fosters openness for analysis and reflections on the different existing support services toward school inclusion in regular schools, as well as it contributes for a greater clarity in the roles and responsibilities of Special Educators for the improvement of the educational work within co-teaching perspective.
The role of special educators within co-teaching approach
Keywords: Educação especial; Inclusão escolar; Ensino colaborativo; Educação - formação; Coensino; Special education; School inclusion; Co-teaching; Collaborative teaching; Teachers education; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL